Programa para el mejoramiento de las habilidades sociales en el manejo de emociones con los estudiantes de quinto de básica de la escuela de educación básica Ruperto Alarcón Falconí de la parroquia de Cotogchoa, durante el periodo octubre-abril del 2016-2017. - Cáceres Maldonado, Diana Carolina (2017)
The present systematization report describes the experience of the Programa para el mejoramiento de las habilidades sociales en el manejo de emociones con los estudiantes de quinto de básica de la Escuela de Educación Básica Ruperto Alarcón Falconí de la parroquia de Cotogchoa, durante el periodo octubre-abril del 2016-2017, in order to know the learning that left the realization of the same, with the objective of developing and strengthening the social skills of the intervened group. The axis of the systematization was conformed by the actions carried out by the author during the training program, which consisted of 10 group sessions in which cognitive-behavioral techniques were used as: Chip economy, Activation control (Relaxation and respiration), Creative Imagination, Internal Dialogue Control and Self-instructions. For the group selection and postintervention evaluation, psychometric tests were used to determine the variables to be intervened (social skills), such as: Social Interaction Skills Questionnaire (Monjas, 1994) and Matson Scale for the Evaluation of Social Skills with Young people (Matson, 1994). The experience of the social skills training program was collected by various sources and processed in order to compare the social skills of the group before and after the intervention, to establish the impact of the intervention on the participants and to answer the key questions raised to throughout the project.